Women's missing mobility and the gender gap in higher education: Evidence from Germany's university expansion - Barbara Boelmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
This paper shows that the local availability of universities acted as a catalyst in the catch-up of women in higher education that has been documented for developed countries in the latter half of the 20th century. It uses the foundation of new universities in the 1960s and 1970s in West German regions which previously did not have a university as a case study to understand how women's mobility and education decisions interact. I first document women's low regional mobility in post-war West Germany along with their low educational attainment. Second, I exploit that the university expansion exogenously brought universities to women's doorsteps in a difference-indifferences (DiD) strategy. Comparing regions which experienced a university opening within 20 km to those where no university was opened, I show that women benefited more than men from a close-by university opening, closing the local gender gap in university education by about 72%. Third, I provide evidence that local universities partly increased university education through reduced costs, while part of the effect is due to higher expected returns, highlighting an important second channel through which universities promote education to local youths.
Keywords: I23; I24; I28; J16; 330; college gender gap; geographic mobility; university expansion